Brain acetylcholine and choline concentrations and dynamics in a murine model of the Fragile X syndrome: Age, sex and region-specific changes. (20th August 2015) - Scremin, O.U.; Roch, M.; Norman, K.M.; Djazayeri, S.; Liu, Y.-Y.
Highlights: Endogenous ACh and Ch contents and dynamics were assessed in FMR1KO mice and WT controls. ACh concentration and synthesis were similar for both mice lines in all regions studied. ACh synthesis, and Ch uptake from blood decreased with age in WT mice. The age dependence of Ch uptake from blood was absent in FMR1KO mice. An increase in Ch uptake from blood was found in the cerebral cortex of FMR1KO female mice. Abstract: Fragile X syndrome is a learning disability caused by excess of CGG repeats in the 5′ untranslated region of the Fragile X gene (FMR1) silencing its transcription and translation. We used a murine model of this condition, Fmr1 knock-out mice (KO) to study acetylcholine (ACh) metabolism and compared it to that of wild-type control mice (WT). Brain endogenous ACh (D0ACh), free choline (D0Ch), their deuterated variants D4ACh and D4Ch and mole ratios (AChMR and ChMR) were measured by gas chromatography–mass spectrometry in the cerebral hemisphere, cerebral cortex, hippocampus and cerebellum, following D4Ch administration. Regression analysis indicated a significant decrease with age (negative slope) of D4ACh, AChMR, D4Ch and ChMR in WT mice. Age dependence was only present for D4ACh and AChMR in KO mice. Analysis of variance with age as covariate indicated a significant greater D4Ch in the cerebral cortex of KO females when compared to WT females. Contrasts between sexes within genotypes indicated lower D0Ch in cortex and cerebellum of female KO mice but not in WT and lower D4Ch in hippocampus of female KO and WT mice. In conclusion, after adjusting for age, D0ACh concentrations and synthesis from deuterium-labeled Ch were similar in KO and control WT mice in all brain regions. In contrast, significant changes in Ch dynamics were found in hippocampus and cerebral cortex of KO mice that might contribute to the pathogenesis of FXS.